A fuzzy-based suspension vehicle depending on terrain. (29th March 2005) - Boada, M.J.L.; Boada, B.L.; Castejon, C.; Diaz, V.
This paper presents a Fuzzy Logic Controller for a semi-active suspension vehicle, depending on terrain. The terrain, which could be traversed by the vehicle, is classified as flat or uneven terrain. The behaviour of the suspension vehicle is different in each class of terrain. The main aim of the controller is to improve passenger comfort, to control the vehicle body attitude and to provide guidance along the track. The proposed Fuzzy Logic Controller has been studied using a quarter vehicle model. The results show the effectiveness of our algorithm.